A NEW FAULT IDENTIFICATION AND PROTECTION SCHEME FOR HVDC TRANSMISSION LINE - Pramod N Todkar; Prof. P.R. Bharambe (International Journal of Innovations in Engineering Research and Technology, 2021)
In this paper main aim is to analyze the performance of high voltage direct current (HVDC) system in case of internal and external fault. Differences between transient energy and other parameters of the line are analyzed in both internal and external fault. To get transient energy, voltage and current are determined at both ends of the line. Developed system identifies the internal and external fault very easily on the basis of transient energy. In the implemented scheme DC fault protection identify a fault & takes the necessary action to clear the fault. The system is implemented in MATLAB Simulink environment, the subsystem made for rectifier and inverter control scheme takes immediate actions to controlled DC power flow through transmission line. From the results obtained it is concluded that measurement transient energy can be used for implementing protection scheme.